Negotiating tensions around new forms of academic writing. (August 2018) - Barton, David; McCulloch, Sharon
Abstract: Almost every aspect of an academic's role involves specialised forms of writing, and the range of digital platforms used to produce this has increased. Core genres such as the journal article and monograph remain central, but the ways they are now commonly produced via file-sharing software and online submission systems are changing them. Digital media also allows academics to stay up to date with their field, connect with others, and share research with wider audiences. Furthermore, academics are increasingly expected to maintain online identities via academic networking sites, and to create and disseminate knowledge via hybrid genres such as tweets and blogs. However, these platforms also represent a potential threat to academics' values and sense of identity. This paper reports on an ESRC funded research project investigating the writing practices of academics across different disciplines at three English universities. Through academics' accounts of their experience with and feelings about the role of digital media in their professional writing, this paper explores the factors that complicate their engagement with new genres of writing. The findings reveal a tension between the values of social media, which see knowledge as user-generated and decentralised, and the forms of knowledge creation that are rewarded in academia.